Effect of the Comonomer Nature on the Cytotoxicity and Mechanical Properties of a Cryogel Based on Sodium 2-Acrylamido-2-methyl-1-propanesulfonate Copolymers - Olga Iakobson; Elena Ivan’kova; Yulia Nashchekina; Gleb Vaganov; Svetlana Laishevkina; Natalia Shevchenko (Colloids and Interfaces)
Currently, for the treatment of corneal diseases (keratitis–corneal opacities), synthetic corneal analogs based on polymer films or hydrogels are being developed. The requirements for the material include biocompatibility, the presence of a developed system of macropores, transparency, rapid swelling, and mechanical strength. Here, with the aim of preparing such materials, a series of gels based on a copolymer of 2-acrylamido-2-methyl-1-propanesulfonic acid (AMP) and 2-hydroxyethyl methacrylate (or vinyl acetate, or ethyl acrylate) were obtained using cryotropic gelation. It was shown that transparent cryogels can be obtained based on the sulfonate-containing comonomer 2-acrylamido-2-methyl-1-propanesulfonic acid at a crosslinking agent concentration of 2.2 mol.%, while the nature of the acrylate comonomer did not show any effect on transparency. It was found that when using AMP and ethyl acrylate, cryogels with a developed system of macropores with a diameter of 50 to 250 μm were formed, and the mechanical strength of such cryogels was sufficient for their subsequent use as corneal implants. Moreover, the PAMP hydrogel containing 2-hydroxyethyl methacrylate or ethyl acrylate units did not affect the viability of cells even after 1 month.